A randomized and clinical study comparing spinal anesthesia with hyperbaric bupivacaine with fentanyl and hyperbaric ropivacaine with fentanyl in cesarean sections - Dharmendra Harjani,; Manisha Bagdi,; Nikita Bagdi Kapoor, (Asian Journal of Medical Sciences, 2022)
Background: Hyperbaric bupivacaine (0.5%) is usually effective for spinal anesthesia and is being increasingly used in cases of patients undergoing lower segment cesarean section under neuraxial block. Addition of fentanyl to local anesthetic drugs such as bupivacaine and ropivacaine is associated with reduced doses of local anesthetic agents thereby decreasing side-effects of local anesthetic drugs. Aims and Objectives: The objectives of the study are as follows: (1) To compare the efficacy of with hyperbaric bupivacaine with fentanyl and hyperbaric ropivacaine with fentanyl in patients undergoing cesarean section. (2) To compare the side effects in both the groups. Materials and Methods: Patients were divided into two groups depending on whether they received hyperbaric bupivacaine with fentanyl (Group BF) or hyperbaric ropivacaine with fentanyl (Group RF). The onset and duration of motor as well as sensory blockade and duration of analgesia was noted. Hemodynamic parameters such as heart rate (HR) and systolic as well as diastolic pressure, respiratory rate, and SPO2 were monitored. APGAR score at 1 min and 5 min was analyzed to know immediate neonatal outcome. Post-operative pain and adverse effects were compared in both groups. Results: Mean time for achieving highest level of sensory analgesia and duration of motor block and analgesia was found to be statistically significantly less in RF group as compared to BF group. Comparison of HR, SPO2, and respiratory rates showed that these parameters were comparable in both the groups with no statistically significant difference (P>0.05). The mean systolic and diastolic blood pressures of BF group were lower as compared to RF group and the difference was found to be statistically significant (P<0.05). At 4 h and 6 h postoperatively, the severity of pain was found to be less in RF group as compared to BF group and the difference was found to be statistically significant (P<0.05). Overall incidence of side effects was found to be comparable in both the groups (P<0.05). Conclusion: Hyperbaric ropivacaine with fentanyl is a better alternative to hyperbaric bupivacaine with fentanyl in ASA II patients undergoing cesarean section.